Collections Data, Tools, and Strategy : Applying R, Tableau and Excel To Print Assessment - Jahnke, Lori (Morressier, 2017)
As is the case at most academic libraries, collection assessment has become an essential component of collection management and development work. Although much of the assessment focus has disproportionately fallen on e-resources, print collections remain fruitful areas for evaluation and review. At Emory, print collections, including a complex approval plan, continue to be a significant component of our overarching collection strategy (in volume and expenditure). However, shifting priorities for library space and the growth of interdisciplinary programs and centers within the University are placing a higher demand on subject librarians for communication and coordinated decision-making regarding print acquisitions. As a result, we are currently preparing for a comprehensive print collection review, of which the approval plan is an integral component. This assessment will inform a more coherent print strategy, which effectively and efficiently meets research and teaching requirements as well as administrative needs. Using data cleaning and visualization tools, such as R, Excel, and Tableau, we have enriched our local usage data with detailed Gobi approval data (e.g., series, publisher, subject, etc.) and profile parameters. Merging these data types and enriching local use data will allow us to analyze the print collection in a more nuanced fashion and ask questions that do not require the LC classification framework. This analysis considers the development of additional tools and approaches that facilitate subject specialist communication with collection management and overall collaborative decision-making, especially in cross disciplinary areas.